Biocompatibility of NeoMTA Plus® versus MTA Angelus as delayed furcation perforation repair materials in a dog model - Khaled M. Abboud; Ashraf M. Abu-Seida; Ehab E. Hassanien; Hossam M. Tawfik (BMC, 2021)
Abstract Background The biocompatibility of NeoMTA Plus® (Avlon BioMed Inc., Bradenton, Fl) as a furcal perforation repair material is not fully understood. This study compares the biocompatibility of Mineral Trioxide Aggregate (MTA Angelus) and NeoMTA Plus® as delayed furcation perforation repair materials. Methods Pulpotomy and root canal obturation were performed in 72 premolars in six mongrel dogs and then a standardized furcal perforation was performed. The coronal access was left open for three weeks. After curetting, cleaning and drying of the perforations, these teeth were divided into three equal groups (N = 24 teeth/ 2 dogs each) according to the material used for perforation repair; group I: NeoMTA Plus®, group II: MTA Angelus and group III: no material (positive control). The coronal access cavities were sealed with a filling material. The inflammatory cell count and qualitative pathology (presence of calcific bridge, configuration of fibrous tissue formed, examination of tissue surrounding the furcation area, histology of intraradicular bone and the inflammatory nature of tissues) were carried out after one week (subgroup A, N = 8 teeth), one month (subgroup B, N = 8 teeth) and three months (subgroup C, N = 8 teeth). The inflammatory cell count was expressed as mean ± SD and statistically analyzed. P-value < 0.05 was considered significant. Results In all subgroups, the control group exhibited the highest number of inflammatory cell count, followed by MTA Angelus group and the least inflammatory cell count was shown by NeoMTA Plus® group. There was a significant difference in the inflammatory cell count between the NeoMTA Plus® and MTA Angelus after one week (P < 0.05) while no significant differences were recorded between them after one month and three months (P > 0.05). In contrast to group II, there was no significant differences in inflammatory cell count between the subgroups in groups I and III (P > 0.05). NeoMTA Plus® exhibited better qualitative pathological features than MTA Angelus after one week and nearly similar features after one month and three months of repair. Conclusion NeoMTA Plus® has a better early biocompatibility than MTA Angelus after one week of delayed furcation perforation repair and a similar late biocompatibility after one month and three months.